The dynamic characteristics of the plantar pressure in three typical badminton footwork patterns - Yu, C.; Zhan, J.; Fu, W. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of this study was to investigate the dynamic characteristics of plantar pressure in the three-badminton footwork patterns (left-forward lunging step, LFLS, right-forward lunging step, RFLS, backward revolve to jump, BRJ). Twelve elite national-level male badminton athletes were recruited while performing the three typical footwork patterns tests in a laboratory-simulated badminton court. The results of the present study demonstrate that the normalized mean peak pressures (MPP) were significantly higher under the hallux and the 1st to 2nd metatarsals than other areas in the toe-off (TO) phase when performing the three footwork patterns. In the process of touching down (TD), both LFLS and RFLS showed significantly higher loads on the rearfoot and the lateral of the foot. Thus, the badminton players should be paying attention to modulating the load strategies on the front-foot, rear-foot, and lateral of the foot regions when performing the different footwork patterns, and select the appropriate footwear that can disperse the higher loads of the target areas to avoid excessive concentration of the plantar pressures.